A novel pharmacological treatment concept for neuroprotection in severe traumatic brain injury—Two case reports. Issue 11 (20th November 2022) - Trimmel, Helmut; Herzer, Guenther; Derdak, Christoph; Kettenbach, Joachim; Grgac, Ivan
Abstract: Severe traumatic brain injury (sTBI) is a major cause of death and disability worldwide, resulting in a significant individual and socioeconomic burden. Current treatment guidelines do not include any recommendations for neuroprotective or neuoregenerative drugs. Here, we present a combined treatment with Cerebrolysin and Citicoline in two cases. Both drugs are experimentally better than clinically proven in their own effectiveness, but there is almost no clinical data on the combination of the two. Our case study hints at a promising approach that may improve neurological outcome after sTBI. The first patient was a 29 years male motorcyclist suffered polytrauma in a high‐speed accident. He had severe bilateral chest trauma and fractures in both thighs and an sTBI. In addition to surgical and standard neurocritical care according to the evidence‐based guidelines, he was given neuroprotective therapy with Cerebrolysin (50 ml/day) and Citicoline (3 g/day), by continuous intravenous infusion (IV), for 21 days. The second patient was a 30 years male ski mountaineer who had suffered a fall over 300 m in open terrain. In addition to the sTBI, he had fractures in the cervical spine, ribs, pelvis, and lower extremities, as well as lung contusions and massive soft tissue trauma. After initial treatment in a local hospital, he was transferred to our department and received the same neuroprotective drugs, like all of our patients with sTBI. Considering the severity of the injuries (Injury Severity Score [ISS]: 43/50, Revised Trauma Score [RTS: 5.0304, 2.7794]) and the unfavorable outcome probability (Hukkelhoven Score) of 93.1% and 82.6%, the outcomes of both patients are surprisingly encouraging 1 year after the accident. They achieved a Glasgow Outcome Score of 6 and 5 and grades 2 and 4 on the modified Rankin Scale, respectively. Currently, both are able to take care of themselves in activities of daily life to a large extent. Neuroprotective drugs may improve the regeneration of cell membranes, improve blood brain barrier integrity, and reduce neuroinflammation leading to secondary damage to the injured brain. Our clinical experience and data suggest that the combined administration of Citicoline and Cerebrolysin may contribute to better recovery, without relevant side effects. However, it would be important to validate these results by means of a controlled, prospective study. Abstract : Citicoline and Cerebrolysin can improve the regeneration of cell membranes, reduce the permeability of the blood–brain barrier, neuroinflammation, and neuronal degeneration. Neurotrophic stimulation increases the survival of highly differentiated neuronal cells; neuromodulation enhances neuronal and synaptic plasticity. Both drugs should be given intravenously and continuously as soon as possible after severe traumatic brain injury.